PENGARUH KOMUNIKASI DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN DI KPPS BMT NU JAWA TIMUR AREA BANYUWANGI - Nurul Hidayah; Anis Hidayati (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2023)
This study aims to determine whether there is a relationship in the influence of communication and work ability on employee performance at KSPP BMT NU East Java Banyuwangi Area. In this study, the researcher took the title to find out how influential work communication and work skills at BMT NU, East Java, Banyuwangi area, because of the return of this title there are many employees who are not good at communicating between co-workers and their superiors. work ability also affects their work it carries out. In this research used a quantitative approach, in the process of collecting data used several methods, namely questionnaires, documentation and data analysis techniques used SPSS v.16 for windows, then used the SPPS v.16 windows application, so with this result Knowledge had a t value. < t table (2.366 > 2.037). So it could be concluded that communication had a significant effect on employee performance at KPPS BMT NU, East Java Banyuwangi Area and work ability had a t count < t table (2.766 < 2.037). So it could be concluded that work ability affects employee performance at KPPS BMT NU, East Java, Banyuwangi Area